Pengaruh Game Online Terhadap Kualitas Tidur Mahasiswa : Literature Review - Dewi, Devi Lestia; Pramana, Yoga; Fauzan, Suhaimi (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The concept of "addiction online game" generated of increasingly digital games expand and excessive use and no controlled especially among child young has Becomes issue latest . Online games among student give impact positive nor negative . impact the negative that is could make it worse quality sleep , consumptive and cause addictive effects or addictive behavior. To identify the effect of online games the quality of sleep of students. Type study this use literature review with analytical techniques using SPIDER and articles obtained from the Pubmed database , Google Scholar, Science Direct, Research Gate and Research using keywords in English, namely online games, sleep quality, sleep quality in collage students and in Indonesian that is online games , sleep quality , and quality sleep on college student. Results literature review obtained 8 appropriate journals with criteria inclusion. Results analysis of 7 articles state that there is significant relationship Among influence online game to quality sleep on student while 1 article states own correlation weak Among influence online game on sleep quality in students. Played online game by excessive nor duration time playing games online can influence quality sleep student . The longer the duration time play games online then will the more bad quality sleep. Keyword : Online Games , Quality Sleep , Quality Sleep On College Student .  ABSTRAK Dampak game online yang semakin meluas dan berlebihan terutama di kalangan anak muda telah menjadi isu terkini. Game online di kalangan mahasiswa memberikan dampak negatif yang dapat memperburuk kualitas tidur, konsumtif dan menimbulkan efek ketagihan atau perilaku kecanduan. Mengidentifikasi pengaruh game online terhadap kualitas tidur mahasiswa. Jenis penelitian ini menggunakan literature review dengan teknik analisa menggunakan SPIDER dan artikel yang diperoleh dari data base Pubmed, Google Scholar, Science Direct, Research Gate dan Neliti dengan menggunakan kata kunci dalam bahasa inggris yaitu game online, sleep quality, sleep quality in collage students dan dalam bahasa indonesia yaitu permainan daring, kualitas tidur dan kualitas tidur pada mahasiswa. Delapan artikel memenuhi kriteria inklusi, menurut tinjauan literature. Hasil analisis 7 artikel menyatakan bahwa terdapat hubungan yang signifikan antara pengaruh game online terhadap kualitas tidur pada mahasiswa sedangkan 1 artikel yang menyatakan memiliki korelasi lemah antara pengaruh game online terhadap kualitas tidur pada mahasiswa. Durasi bermain game online dapat mempengaruhi kualitas tidur mahasiswa. Semakin lama durasi waktu bermain game online maka akan semakin buruk kualitas tidurnya. Kata Kunci: Permainan Daring, Kualitas Tidur, Kualitas Tidur Mahasiswa.